ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DI UKM AJI BERKAH - Wahyuni, Ayu Endah; Irzan, Muhammad; Damayanti, Erni (Globalwriting Academica Consulting & Publishing, 2023)
UMKM Aji Berkah is a Make to Stock company engaged in the food sector. This MSME has an inventory policy with a traditional or manual system. Supplies are often carried out in large quantities without considering existing demand patterns. So that sales profits are not maximized or result in deadstock. To overcome the problems that occur in these SMEs, it is necessary to evaluate the management of purchasing policies by balancing ordering and storage costs. To support this purchasing policy, it is necessary to have good inventory management for MSMEs to determine when to purchase materials. To overcome the erratic pattern of demand, material supplies (Safety Stock) are needed. In this study, an evaluation of product inventory purchasing policies contained in UMKM Aji Berkah and control of flour raw material inventory will be carried out using the Economic Order Quantity (EOQ) method.